2022
DOI: 10.1002/anie.202210509
|View full text |Cite
|
Sign up to set email alerts
|

Sulfenofunctionalization of Chiral α‐Trifluoromethyl Allylboronic Acids: Asymmetric Synthesis of SCF3, SCF2R, SCN and SAr Compounds

Abstract: We report herein a new method for the synthesis of densely functionalized chiral allyl SCF3, SCF2R, SCN and SAr species with a separate CF3 functionality. The synthetic approach is based on selenium‐catalyzed sulfenofunctionalization of chiral α‐CF3 allylboronic acids. The reactions proceeded with remarkably high stereo‐, diastereo‐ and site‐selectivity, based on the formation of a stable thiiranium ion followed by rapid deborylative ring opening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…have been described in the literature [33]. As regards the difunctionalization of olefins, Magnier and co-workers [34] accomplished the carbotrifluoromethylthiolation of acrylamides or aryl alkenes with N-trifluoromethylthiosaccharin as the source of the SCF3 radical (Scheme 12).…”
Section: Methodsmentioning
confidence: 99%
“…have been described in the literature [33]. As regards the difunctionalization of olefins, Magnier and co-workers [34] accomplished the carbotrifluoromethylthiolation of acrylamides or aryl alkenes with N-trifluoromethylthiosaccharin as the source of the SCF3 radical (Scheme 12).…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies we have shown [18a, 19] that disubstituted alkenylboronates, such as boroxines and diethyl esters, underwent enantioselective homologation with trifluoro diazoethane ( 2 ) in the presence of catalytic amounts of iodo‐BINOL. We surmised that using fluorinated trisubstituted alkenes, such as 1 a (Table 1) γ‐disubstituted allylboronates could be obtained, which would be useful synthons for diastereo‐ and enantioselective synthesis of β‐fluorohydrins with a tertiary C−F stereocenter.…”
Section: Methodsmentioning
confidence: 99%
“…al. [97] These researchers found that transfer of various sulfur-containing groups from imide reagents in the presence of catalytic diaryl selenides resulted in the rearranged products 133 and 134. The transferred sulfur groups included SCF 3 , SCF 2 R, SAr and SCN.…”
Section: Allylic Thiolationsmentioning
confidence: 99%